Evaluating cyclic creep behavior of silicone-based thermoplastic elastomers for morphing control surface applications - Jeong-Hwan Yoon; Min-Jun Gim; Ye-Won Park; Yeon-Jee Cho; Kyoung-Ho Shin; Jae-Won Lee; Hui-Yeol Yun (Polymer Testing)
The development of morphing control surfaces in automotive applications has necessitated the development of advanced elastomeric materials with high resilience and elastic recovery under cyclic deformation. In this study, the suitability of silicone-based thermoplastic vulcanizate (TPV-Si) and silicone-based thermoplastic polyurethane (TPU-Si) materials as morphing surface skins was investigated. A new cyclic creep test method for simulating real-world operational conditions for morphing control surfaces was proposed to evaluate the performance of these materials. The Norton-Bailey model was employed to analyze the test results to characterize the creep behavior across different strain levels, focusing on the primary and secondary deformation phases. The results revealed distinct differences in the elastic recovery capabilities and durability of TPV-Si and TPU-Si, offering insights into material selection for enhanced durability in morphing-controlled surface applications. This analysis highlighted the superior performance of TPU-Si under high-strain conditions, making it a promising candidate for automotive morphing technology.